Human Papillomavirus Associated Cancers of the Head and Neck: An Australian Perspective - Aldalwg, M.; Brestovac, Brian (2017)
© 2017, Springer Science+Business Media New York. Human papillomavirus (HPV) associated head and neck squamous cell carcinomas (HNSCCs), have become a serious global health problem. Despite decreases in HPV-negative HNSCCs, the prevalence of HPV-positive HNSCCs has significantly increased. HPV-positive cancers are associated with superior survival outcomes when compared to HPV-negative cancers, which appears likely to be associated with differences in the molecular pathogenesis of the two diseases. While therapies are still problematic, the current HPV vaccine programs hold a promise for the primary prevention of HPV-related HNSCCs and since Australia was the first to introduce a nationwide HPV vaccine program, it is in a unique position to observe the effects of the vaccine on HNSCCs. This review discusses the epidemiological trends associated with HPV in HNSCC, with reference to the differences between HPV-positive and HPV-negative HNSCCs and the prevention potential of HPV vaccines.